Correlation Between Hemoglobin Levels, Hematocrit Values, And Platelet Counts with the Severity of Dengue Hemorrhagic Fever in Pediatric Patients - Anggela, Aprilia; Patricia, Tisha; Trisia, Adelgrit; Handayani, Septi; Shinta, Herlina Eka (Barigas: Jurnal Riset Mahasiswa, 2025)
Dengue hemorrhagic fever (DHF) often causes bleeding, increasing disease severity and mortality risk due to inadequate oxygen supply influenced by thrombocytopenia, elevated hematocrit, and hemoglobin levels. DHF severity is classified into four stages: fever and plasma leakage (stage 1), spontaneous bleeding (stage 2), circulatory failure (stage 3), and severe shock (stage 4). This study examines the relationship between hemoglobin levels, hematocrit values, and platelet counts with DHF severity in 51 pediatric inpatients at dr. Doris Sylvanus General Hospital, Palangka Raya, from January to December 2023. Using a cross-sectional design and simple random sampling, data from medical records were analyzed. Normality tests revealed significant correlations between hematocrit values and platelet counts with DHF severity, while hemoglobin levels showed no significant correlation. These findings highlight the importance of hematocrit and platelet monitoring in DHF management